Dampak Urban Heat Island terhadap Perubahan Pola Cuaca di Sidoarjo dan Malang: Analisis Data Harian BMKG - Assajdah Abdullah; Muhammad Zaki Albukhori; Krisna Dewi; Wyra Steven Hutagalung; Muhammad Yazid Ilmany; Syahrajad Al Syarqiyah; Zulfitrah Mokoginta (Journal of Computation Physics and Earth Science (JoCPES), 2025)
The Urban Heat Island (UHI) phenomenon is an increase in surface temperature in urban areas compared to the surrounding, more rural areas. This phenomenon can affect shifts in weather patterns, including an increase in average temperature, changes in rainfall patterns, and an increase in extreme weather events. This study aims to analyse the impact of UHI on shifting weather patterns in Indonesia using BMKG daily climate data. The method used includes a quantitative approach withtime series analysis to understand the trend of changes in air temperature and rainfall in Sidoarjo and Malang. The results showed a correlation between UHI intensity and changes in weather patterns,where areas with high UHI intensity experienced a significant increase in temperature and changes in rainfall patterns. This research is expected to provide insights for more sustainable urban planning in the face of UHI impacts in Indonesia.